Contemporary financial management : instructor's resource manual - Moyer, R. Charles; McGuigan, James R.; Kretlow, William J. (Ohio : South-Western College Publishing, 1998)
Business
1998-01-05
Keywords: Financial management; Manual; Teacher's manual